The presence of the lawyer in medical examinations: a narrative review (Saúde Ética & Justiça, 2020)
A judge does not have all the technical or scientific knowledge necessary to solve every lawful dispute. Therefore, the Brazilian Code of Civil Procedure allows the use of experts, such as medical specialists, who act as appointed experts, to elucidate matters specific to the case. The aim of this study was to carry out a literature review to discuss and clarify the possibility of the lawyer witnessing medical examination. The following documents were consulted: the Brazilian Constitution; the Criminal Procedure Code; the Code of Civil Procedure; documents from the Brazilian Bar Association (OAB); documents of the Federal Council of Medicine and jurisprudence in the Supreme Federal Court (STF). There is a normative provision for the lawyer to freely enter a series of places and, when asked, to accompany his/her client in judicial investigations to give the client comfort and legal security. Nevertheless, there is no legal provision for a lawyer to act as medical assistant during a medical examination, therefore it is the appointed medical expert’s prerogative to decide (justified in writing) on the presence of an accompanying lawyer during the medical examination.